2018
DOI: 10.1155/2018/5458015
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness and Ganglion Cell Complex in Pubescent Children with Type 1 Diabetes without Diabetic Retinopathy Analyzed by Spectral Domain Optical Coherence Tomography

Abstract: Aim To assess the retinal and choroidal thickness and ganglion cell complex (GCC) in pubescent children with type 1 diabetes (T1D) without diabetic retinopathy (DR), using spectral domain optical coherence tomography (SD-OCT). Materials and Method Sixty-four right eyes of 64 subjects with T1D and 45 right eyes of 45 age-matched healthy volunteers (control group) were enrolled in this study. The mean age of the subjects and controls was 15.3 (±SD = 2.2) and 14.6 (±SD = 1.5), respectively. SD-OCT was performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 41 publications
5
33
3
Order By: Relevance
“…contains some general information about the studies reviewed in this article. Endo et al,Wang and Tao, Gupta et al,Rewbury et al, Ohara et al, Tan et al, Hua et al, Kim et al, Sudhalkar et al, Totan et al., Gerendas et al, Lee et al, Adhi et al, Regatieri et al, and Gołębiewska et al evaluated CT measurements and some of these studies also evaluated CVI in diabetic patients with and without DR as described inTable 2[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Kim et al only investigated for CVI in these patients[29].…”
mentioning
confidence: 99%
“…contains some general information about the studies reviewed in this article. Endo et al,Wang and Tao, Gupta et al,Rewbury et al, Ohara et al, Tan et al, Hua et al, Kim et al, Sudhalkar et al, Totan et al., Gerendas et al, Lee et al, Adhi et al, Regatieri et al, and Gołębiewska et al evaluated CT measurements and some of these studies also evaluated CVI in diabetic patients with and without DR as described inTable 2[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Kim et al only investigated for CVI in these patients[29].…”
mentioning
confidence: 99%
“…Notably, Vujosevic et al 8 demonstrated a significant inverse correlation between perifoveal capillary loss in superficial capillary plexus (SCP) and inner retinal layer thickness in patients with DM and no clinical signs of DR. Since retinal thickness is decreased in pubescent T1DM children without DR and correlates with HbA1C level, some authors suggested that OCT can be considered a tool for early detection of retinal abnormalities in patients with diabetes 9 .…”
mentioning
confidence: 99%
“…There are conflicting reports on the effects of diabetes on PMCT. Previous studies on PMCT in adults suggested that the CT mainly increased at the early stage of diabetes and decreased at longer duration of diabetes (Vujosevic et al 2012;Tavares et al 2017;Horvath et al 2018;Tavares et al 2018;Golebiewska et al 2018). We supposed that the reason of conflicting of PMCT is mainly due to the difference of the duration.…”
Section: The Role Duration May Plays In the Posterior Pole Choroid Thmentioning
confidence: 69%
“…; Golebiewska et al. ). We supposed that the reason of conflicting of PMCT is mainly due to the difference of the duration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation